2002
DOI: 10.3139/217.1708
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation and Analysis of the Flow along the Kneading Block of a Twin-screw Extruder

Abstract: The flow of a silicone oil of high viscosity along a block of staggered kneading discs of a co-rotating twin screw extruder was investigated with the use of an acrylic transparent barrel. A digital video camera recorded the flow path of a red dye, dispersed in the silicone oil, along the screws and in the intermeshing zone. Different geometrical configurations were studied, namely various staggering angles (+30°, 90°and -30°) and thicknesses (7.5, 15.0 and 22.5 mm) of kneading blocks. The effects of these geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…From our calculations, we are able to rank four typical kneading blocks. Our conclusions from the numerical experiences appear to be in very good agreement with global classical interpretation of the flow [37]. It is also in line with guidelines found in reference books.…”
Section: Resultssupporting
confidence: 89%
“…From our calculations, we are able to rank four typical kneading blocks. Our conclusions from the numerical experiences appear to be in very good agreement with global classical interpretation of the flow [37]. It is also in line with guidelines found in reference books.…”
Section: Resultssupporting
confidence: 89%
“…The study of the melting phenomena in single extruders has a relatively long history. , However, a comprehensive study in the TSE started only recently with Todd . Since then, the study of the melting phenomena in the TSE has attracted much attention. It was widely accepted that the mechanical energy plays a critical role for the fast melting of polymers in the TSE…”
Section: Introductionmentioning
confidence: 99%
“…An effective viscosity was estimated for the extrusion flow at the initial stage of melting. The existence of solid polymer pellets in the flow significantly increased the viscosity of the flow. Viscous energy dissipation (VED) could be another key mechanism to generate a significant amount of heat from mechanical energy in the TSE. More recently, Gogos and co-workers , reported that plastic energy dissipation (PED) was the dominant heat source to melt polymers in the TSE.…”
Section: Introductionmentioning
confidence: 99%
“…The two flows are described by various process parameters, including screw speed N, shear viscosity η, volume flow rate _ V , pressure gradient p 0 , mechanical drive power per period P=L, and dissipation per period _ Q Diss =L. The volume flow rate _ V is directly linked to the velocity profile in the flow direction v z , as given in Equation (15). The boundary conditions for the velocity are defined by the screw speed and the stationary barrel walls because wall adhesion is assumed.…”
Section: Governing Equationsmentioning
confidence: 99%
“…[14] Twin-screw extrusion modeling, as in the publications mentioned above, has focused mainly on the conveying elements, while kneading blocks have received less attention. The complex flow patterns of kneading blocks, as analyzed by Carneiro, [15,16] pose considerable challenges to these modeling approaches. Szydlowski [17][18][19] was the first to study kneading blocks in detail, of which the geometry is often drastically simplified; for example, Potente [20] replaced the kneading discs with continuous channels and thus modeled kneading blocks as conveying elements.…”
mentioning
confidence: 99%